Hospital characteristics are associated with patient outcomes following out-of-hospital cardiac arrest. Issue 18 (21st June 2011) - Stub, Dion; Smith, Karen; Bray, Janet E; Bernard, Stephen; Duffy, Stephen J; Kaye, David M
Abstract : Objective: Post-resuscitation care may influence outcome following transport to hospital after resuscitation from out-of-hospital cardiac arrest (OHCA). This study aimed to determine whether receiving hospital characteristics such as 24-h cardiac catheterisation services, total bed number or OHCA patient volume influence the rate of survival. Setting: Data were analysed from the Victorian Ambulance Cardiac Arrest Registry of patients from January 2003 to March 2010 who were transported to hospital with return of spontaneous circulation (ROSC) after OHCA. Results: Ambulance paramedics attended 9971 patients with OHCA of suspected cardiac cause during the study period. Of these, 2902 (29%) achieved ROSC and were transported to one of 70 hospitals. 1816 (63%) were treated at hospitals with 24-h cardiac interventional services. After adjusting for differences in baseline characteristics, hospital factors significantly associated with survival were treatment at hospitals with 24-h cardiac interventional services (OR 1.40; 95% CI 1.12 to 1.74, p=0.003) and patient reception between 08:00 and 17:00 hours (OR 1.34; 95% CI 1.10 to 1.64, p=0.004). OHCA patient volume and total hospital bed number were not independently associated with outcome. Conclusion: Hospital characteristics are associated with improved survival in patients with OHCA. This finding has implications for the establishment of regionalised systems of care for patients who have been resuscitated from OHCA.